Effect of Clubbell Training on Glenohumeral Internal and External Rotation, Muscle Function, and Ball Velocity in Baseball Pitchers - Choi, Won-Ho; Lee, Jung-No (The Asian journal of kinesiology, 2022)
OBJECTIVES This study examined the effects of clubbell exercises in a pitcher training program on the range of motion (ROM), muscle function, and its subsequent influence on pitching velocity. Additionally, this study aimed to develop an optimal training program to prevent injury while improving pitcher performance.METHODS Eighteen pitchers were included and equally divided into clubbell exercise and control groups. Clubbell training was conducted through 60-minute sessions twice a week for 12 weeks. Internal/external rotational (IR/ER) ROM, IR/ER muscle strength, muscle endurance, muscle power, and pitching velocity were measured before and after the intervention.RESULTS The IR (p = 0.051) and total ROM (TROM; p = 0.05) of the throwing arm decreased in the control group but increased in the clubbell exercise group, with an observed tendency of interaction. In the non-throwing arm, the ER ROM was significantly different between the two groups (p <0 .05), also with an observed tendency of interaction (p = 0.055). IR peak torque per body weight at 60°/sec significantly increased in both groups over the exercise period (p < 0.01). Total work per body weight and average power of IR at 180°/sec increased in both groups over the exercise period (p < 0.01). The pitching velocity decreased in both groups throughout the exercise period (p < 0.05).CONCLUSIONS Although 12 weeks of clubbell training had limited effects on ROM, the findings revealed that this exercise could be effective in improving pitching performance, preventing injuries, and maintaining long-term performance. Further studies are recommended for a more detailed assessment.